The Impact of Socioeconomic Factors on BRICS Migrants in the Russian Federation - Valei, Azamat; Mamman, Suleiman (Journal of Economic Sociology)
Within the last decade, the Russian Federation has witnessed an unprecedented growth in migrants’ inflow placing it amongst the top destinations for transnational migrants. This trend includes members of the BRICS (Brazil, Russia, India, China, and South Africa) economic bloc whose obvious increase started in the post-2010 era. Thus, it is unclear whether the economic cooperation has facilitated migration flow or other socioeconomic factors which could be explained by the Pull-Push theory are responsible. The study carried out an empirical assessment of the socioeconomic factors that determine BRICS migrants to Russia on a macro scale using data from the member states that include Brazil, India, China, and South Africa. The heterogeneous panel model was adopted as the analytical method. The result reveals a negative effect of Russian wages on immigrants’ inflow while GDP per capita had a positive effect. For the push factors, unemployment had a positive and significant effect in the short run but not so in the long run. Also, the population had a negative and insignificant effect in the short run but a positive and significant effect in the long run. The income differentials were also found to be positive and significant in the model. Lastly, there was evidence of policy effect on the migrants’ movement; however, concerning BRICS countries, there was rather a negative effect of migration policy on the immigrants mobility.